2016
DOI: 10.1186/s12977-016-0261-1
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Tat immunization induces cross-clade neutralizing antibodies and CD4+ T cell increases in antiretroviral-treated South African volunteers: a randomized phase II clinical trial

Abstract: Background Although combined antiretroviral therapy (cART) has saved millions of lives, it is incapable of full immune reconstitution and virus eradication. The transactivator of transcription (Tat) protein is a key human immunodeficiency virus (HIV) virulence factor required for virus replication and transmission. Tat is expressed and released extracellularly by infected cells also under cART and in this form induces immune dysregulation, and promotes virus reactivation, entry and spreading. Of note, anti-Tat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 110 publications
2
21
0
Order By: Relevance
“…High titre Tat-specific serum IgG appears to correlate with control of HIV infection in humans1133 and SIV in macaques3435. Therefore, we compared the titres of Tat-specific IgG generated after vaccination with wt-HRV-A1/pVAX, rHRV-DNA or 3X pVAX-Gag-Tat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High titre Tat-specific serum IgG appears to correlate with control of HIV infection in humans1133 and SIV in macaques3435. Therefore, we compared the titres of Tat-specific IgG generated after vaccination with wt-HRV-A1/pVAX, rHRV-DNA or 3X pVAX-Gag-Tat.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to robust CMI, rHRV-DNA induced higher Tat-specific serum IgG and mucosal sIgA titres than wtHRV-A1/pVax or 3X pVAX-Gag-Tat vaccination (Fig. 4A), additional markers which appear to correlate with control of HIV in humans1133 and SIV in animals3443. Although we did not assess functionality of the Tat-specific antibodies in terms of anti-Tat neutralization, a previous study conducted in our laboratory indicated that intradermal vaccination with pVAX-sTat-IMX313, one of the vaccines used in the regimens of this study, elicited antibodies with Tat neutralization activity that correlated with control of EcoHIV25.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Tat-BH10 vaccine responders produced antibodies that recognize Tat for HIV subtypes A, B, C and D. These antibodies may be therapeutic. Tat-BH10 responders had increased levels of CD4 + cells compared to baseline, as well as reduced viral loads in plasma and proviral DNA load in PBMCs [79,83]; and Tat-Oyi vaccine responders had reduced viral rebound following cessation of cART [86]. The evidence suggests that restoration of cell mediated immunity contributed to decreased proviral load.…”
Section: Anti-tat Vaccines That May Compliment Cartmentioning
confidence: 95%
“…Both types of Tat vaccine were tested in non-human primate (SHIV) models, producing conflicting results regarding efficacy [80,81,87,[151][152][153]. Here we recap recent small-scale phase l/lla vaccination clinical trials with Tat-BH10 or Tat-Oyi [78,79,82,86,154,155] (Table 1). In these trials, HIV-infected participants were treated with cART, which controlled viremia.…”
Section: Anti-tat Vaccines That May Compliment Cartmentioning
confidence: 99%
“…Combined treatment of Tat Oyi vaccine and cART has found to increase CD4+ T-cell numbers. Phase III studies that has been conducted in South Africa (Trial registration ClinicalTrials.gov NCT01513135) unfolded that Tat vaccination induces cross-clade neutralizing anti-Tat antibodies in patients with different infecting viruses and belonging to different genetic backgrounds [84].…”
Section: Tat Therapeutic Hiv Vaccinementioning
confidence: 99%